2021
DOI: 10.3390/ijms22094840
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Subproteome Analysis Reveals Underlying Defense Mechanisms of Wheat Seedling Leaves under Salt Stress

Abstract: Salt stress is the second most important abiotic stress factor in the world, which seriously affects crop growth, development and grain production. In this study, we performed the first integrated physiological and endoplasmic reticulum (ER) proteome analysis of wheat seedling leaves under salt stress using a label-free-based quantitative proteomic approach. Salt stress caused significant decrease in seedling height, root length, relative water content and chlorophyll content of wheat seedling leaves, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…These findings mirror the results of previous studies, which showed that G protein receptors play an important role in the response to abiotic stresses, especially high salinity ( Liu et al 2018 ). Activation of chaperones and folding catalysts is a key way for organisms to deal with misfolded proteins resulting from the accumulation of reactive oxygen species owing to salt stress ( Zhang et al 2021 ). Next, we found that the most significant changed DEGs were enriched in the genes specific to the high salinity group (Fisher’s exact test, P = 1.4 × 10 −7 ), rather than those shared with the low salinity group ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings mirror the results of previous studies, which showed that G protein receptors play an important role in the response to abiotic stresses, especially high salinity ( Liu et al 2018 ). Activation of chaperones and folding catalysts is a key way for organisms to deal with misfolded proteins resulting from the accumulation of reactive oxygen species owing to salt stress ( Zhang et al 2021 ). Next, we found that the most significant changed DEGs were enriched in the genes specific to the high salinity group (Fisher’s exact test, P = 1.4 × 10 −7 ), rather than those shared with the low salinity group ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…The grain nuclear proteome identification was performed by using EASY-nLC 1000 (Thermo/Finnigan, Sanjose, CA, United States) according to the recent report ( Zhang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Various protein post-translational modifications also participate in regulating drought responses such as phosphorylation and acetylation modifications ( Zhang et al, 2014a , b ; Zhu et al, 2018 ). In recent years, subcellular proteomics has been developed to decipher different organelle proteins involved in abiotic stress defense such as endoplasmic reticulum, plasma membrane, chloroplast, and mitochondria ( Wang and Komatsu, 2016 ; Zhang et al, 2021 ; Zhu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have reported the role of ER stress signalling in salt stress response, the underlying molecular mechanism and client proteins for the ER-associated regulatory mechanisms are still unknown. Zhang et al [95] performed the first ER proteome analysis of wheat seedlings to understand the role of ER proteostasis pathways in salt-induced growth reduction. They proposed a putative mechanism whereby salt stress generates ROS, which triggers Redox reactions in the cell leading to the accumulation of misfolded proteins.…”
Section: Er Stress Signalling In Response To Salt Stressmentioning
confidence: 99%